Anti-Inflammatory and Antioxidant Effects of Carpesium cernuum L. Methanolic Extract in LPS-Stimulated RAW 264.7 Macrophages. (8th August 2020) - Park, Yea-Jin; Cheon, Se-Yun; Lee, Dong-Sung; Cominguez, Divina C.; Zhang, Zhiyun; Lee, Sangwoo; An, Hyo-Jin
Abstract : A hypernomic reaction or an abnormal inflammatory process could cause a series of diseases, such as cardiovascular disease, neurodegeneration, and cancer. Additionally, oxidative stress has been identified to induce severe tissue injury and inflammation. Carpesium cernuum L. (C. cernuum ) is a Chinese folk medicine used for its anti-inflammatory, analgesic, and detoxifying properties. However, the underlying molecular mechanism of C. cernuum in inflammatory and oxidative stress conditions remains largely unknown. The aim of this study was to examine the effects of a methanolic extract of C. cernuum (CLME) on lipopolysaccharide- (LPS-) induced RAW 264.7 mouse macrophages and a sepsis mouse model. The data presented in this study indicated that CLME inhibited LPS-induced production of proinflammatory mediators such as nitric oxide (NO) and prostaglandin E2 (PGE2 ) in RAW 264.7 cells. CLME treatment also reduced reactive oxygen species (ROS) generation and enhanced the expression of heme oxygenase-1 (HO-1) protein in a dose-dependent manner in the LPS-stimulated RAW 264.7 cells. Moreover, CLME treatment abolished the nuclear translocation of nuclear factor- κ B (NF- κ B), enhanced the activation of nuclear factor-erythroid 2 p45-related factor 2 (Nrf2), and reduced the expression of extracellular signal-related kinase (ERK) and ERK kinase (MEK) phosphorylation in LPS-stimulated RAW 264.7 cells. These outcomes implied that CLME could be a potential antioxidant and anti-inflammatory agent.